Distribution and dynamics for the ecological assessment of Asan Wetland through periphyton -a water quality indicator - Sazia Tabassum; C. B. Kotnala; A. K. Dobriyal; Mohammed Salman; Richa Bamola (Frontiers in Environmental Chemistry)
The Asan Wetland is an important freshwater wetland in Uttarakhand’s Dehradun district. It is known for its diverse flora and fauna and as a stopover for migratory birds. Periphyton, an essential biological component of aquatic ecosystems, serves as a bioindicator of water quality and ecosystem integrity. This study fills a gap in our knowledge of the Asan Wetland’s ecological health by analyzing periphyton populations and a number of physicochemical characteristics across three selected sites from November 2021 to October 2023. Selected sites named as Site 1(S1), Site 2(S2), Site 3 (S3). Monthly variations in parameters such as water temperature, pH, turbidity, transparency, total dissolved solids (TDS), electrical conductivity, dissolved oxygen (DO), total hardness, alkalinity, biological oxygen demand (BOD), chemical oxygen demand (COD), and nutrients were collected, identified and assessed using Ms-excel and Past software. Phosphorus levels in the Asan Wetland indicated a moderate to high nutrient load, peaking in August (1.20–1.25 mg/L) across all three sites and dropping to their lowest in January (0.35–0.65 mg/L). Nitrate levels were moderate, with the highest concentrations in December (1.40–1.55 mg/L) and the lowest in July (0.25–0.35 mg/L), showing similar seasonal patterns across sites. The periphyton was represented in this study by 18 different periphytic taxa that belong to three different classes. These classes include Bacillariophyceae (Cymbella, Navicula, Nitzschia, Fragilaria Meridion, Synedra, Gomphonema, Tabellaria, and Diatoma), members of the Chlorophyceae Ulothrix, Spirogyra, Cosmarium, Microspora, Chlorella, Oedogomium, Zygnema, and Cladophora are, while Phormidium is a member of the Cyanophyceae. The peak periphytic density (individuals/cm2) recorded was 322.67 ± 89.08 × 103 in January, with all three classes exhibiting maximum values at S3, the minimum periphytic density (individuals/cm2) recorded was 18 ± 5.57 × 10³ in August. The annual percentage composition of periphytic flora in the Asan wetland over 2 years indicates that Bacillariophyceae constituted the predominant group (89%–90%), succeeded by Chlorophyceae (7%–9%) and Cyanophyceae or Myxophyceae (1%–4%) across three sites. The canonical correspondence analysis (CCA) of periphyton among different sites during both years of the study suggested that S3 was more diverse, followed by S1 and S2, represented 64.93%, 35.07% of the variance with eigenvalues of 0.01794, 0.00968 respectively. PCA suggested that PC1 and PC2 were represented by 93.98% and 6.015% of the variance with eigenvalues 279.149 and 17.8675, respectively The multivariate cluster analysis showed the similarity of periphyton at three different sites during the 2-year study. The findings of this study emphasize the need for targeted management strategies to maintain the ecological health of the Asan Wetland.